Digital Transformation Policy and Strategy of the Republic of Moldova - Ludmila MOGILDEA; Ina MOGILDEA; Constanta Laura ZUGRAVU; Gheorghe Adrian ZUGRAVU (Communications of International Proceedings, 2023)
The Republic of Moldova is a country that has all the necessary tools for a rapid and impactful digital transformation: advanced infrastructure, a developed ICT private sector, the commitment of the authorities, oriented towards digital transformation, as well as a society prepared to accept and use digitalization. Market demand and available content are key elements for network development. With 98% of the population covered by a 4G signal and a similar fiber optic network penetration, users have the freedom to choose their preferred means of connection. Internet prices are relatively affordable and its use is widespread, with 80% of the population having access to Internet services.
Keywords: Digital Strategy; Agriculture Digitalization